Integrasi Pendidikan Agama Hindu Dalam Pelaksanaan Ngembak Api Di Desa Kayuputih Kecamatan Banjar Kabupaten Buleleng - Supandi, I Nyoman Alit; Sukerni, Ni Made (Jurnal Penelitian Agama Hindu, 2025)
Each region in Bali has its own local religious wisdom that characterizes the dynamics of its religious activities. One of the local wisdoms found in Kayuputih Village lies in the implementation of ngembak api. Its uniqueness is clearly visible from the form of its implementation until the end of its implementation which includes a series (procession), time and place, and the facilities used. The purpose of this study is to understand the integration of Hindu religious education in the implementation of ngembak api. This study uses a qualitative descriptive research method with a phenomenological approach, because the focus of this study is to explore the experiences, perceptions, and views of the community regarding the ngembak api tradition. There are two types of data sources in this study,namely primary data and secondary data. Primary data is obtained through observation and interviews, while secondary data is obtained through document studies and literature reviews. The selection of informants in this study was carried out using a purposive technique. The data collection technique used is data reduction. The results of this study are1) factors causing integration in the kayuputih community in the ngembak api ceremony, 2) ngembak api process occurs, 3 )implications of the integration of ngembak api. Conclusion of this study Through the integration of the ngembak api tradition into Hindu religious education, the community is not only taught spiritual knowledge,but also directed to practice noble values ​​in real life. This tradition is not only a cultural asset,but also an effective means to build individual morality and community harmony in line with Hindu teachings. The values ​​of the ngembak api tradition can be passed on to future generations as well as being an integral part of character education based on local wisdom.